2014
DOI: 10.1063/1.4879900
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a two-dimensional electromagnetic breather with an electron inhomogeneity in an array of carbon nanotubes

Abstract: Propagation of ultrashort laser pulses through various nano-objects has recently became an attractive topic for both theoretical and experimental studies due to its promising perspectives in a variety of problems of modern nanoelectronics. Here, we study the propagation of extremely short two-dimensional bipolar electromagnetic pulses in a heterogeneous array of semiconductor carbon nanotubes. Heterogeneity is defined as a region of enhanced electron density. The electromagnetic field in an array of nanotubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…They can also be used as the medium in which the formation of light bullets occurs. Corresponding calculations were made for one-, twoand three-dimensional cases [13][14][15][16][17][18][19][20] and it was found that the CNT medium allows for the possible stable propagation of light bullets. There is only one rather weighty constraint that comes from practical considerations: the speed of propagation of light bullets is only defined by the refractive index of the medium and it can only be tuned in a fairly narrow interval of values.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be used as the medium in which the formation of light bullets occurs. Corresponding calculations were made for one-, twoand three-dimensional cases [13][14][15][16][17][18][19][20] and it was found that the CNT medium allows for the possible stable propagation of light bullets. There is only one rather weighty constraint that comes from practical considerations: the speed of propagation of light bullets is only defined by the refractive index of the medium and it can only be tuned in a fairly narrow interval of values.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous estimates (see, e.g., Refs. [21][22][23][24] indicate that the resulting error can be considered to be negligible (less than 1%). It is worth noting that due to the field inhomogeneity along certain directions (e.g., the field is nonuniform along the z-axis, the current is also not uniform.…”
Section: Formulation Of the Problem And General Equationsmentioning
confidence: 99%
“…This approximation has been validated by other numerical experiments for the case of CNTs and a pulse duration of tens of femtoseconds. [21][22][23] III. RESULTS AND DISCUSSION…”
Section: Formulation Of the Problem And General Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by numerical experiments for the case of carbon nanotubes and a pulse duration of tens of femtoseconds. 11,14,15 3. Results of the Numerical Analysis Equation (7) has been solved numerically using the explicit finite difference crosstype schemes 16 with temporal evolution.…”
Section: Three-dimensional Extremely-short Optical Pulses In Cnt Arraysmentioning
confidence: 99%